2018
DOI: 10.1161/strokeaha.117.019806
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Perfusion Predicts Poor Outcomes in a Randomized Trial of Endovascular Therapy

Abstract: The majority of patients with CTP imaging in the ESCAPE trial had penumbral patterns, which were associated with better outcomes overall. Patients with penumbra treated with endovascular therapy had the greatest odds of good functional outcome. Nonpenumbral patients were much less likely to achieve good outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Our results are in line with the previous finding that most patients who had a proximal large vessel occlusion with a moderate-to-good collateral circulation on the ASPECTS collateral score are more likely to have a large penumbral volume (17). For example, the ESCAPE trial (Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion with Emphasis on Minimizing CT to Recanalization Times) used collateral assessments on mCTA for endovascular thrombectomy patient selection (5), and most patients included in the ESCAPE trial who underwent CTP imaging had a penumbral pattern (17). This is because patient with a good collateral circulation are more likely to have a large penumbra lesion with a corresponding small ischemic core and so were very likely to have target mismatch.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with the previous finding that most patients who had a proximal large vessel occlusion with a moderate-to-good collateral circulation on the ASPECTS collateral score are more likely to have a large penumbral volume (17). For example, the ESCAPE trial (Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion with Emphasis on Minimizing CT to Recanalization Times) used collateral assessments on mCTA for endovascular thrombectomy patient selection (5), and most patients included in the ESCAPE trial who underwent CTP imaging had a penumbral pattern (17). This is because patient with a good collateral circulation are more likely to have a large penumbra lesion with a corresponding small ischemic core and so were very likely to have target mismatch.…”
Section: Discussionsupporting
confidence: 93%
“…It is likely that insufficient collateral flow that leads to rapid tissue infarction accounts for the lack of benefit due to recanalization in many of these patients. Supporting this, multiphase CT angiography data from the ESCAPE (Endovascular treatment for Small Core and Anterior circulation Proximal occlusion with Emphasis on minimizing CT to recanalization times) trial identified a strong association between pre-treatment cerebral pial collaterals and favorable outcome after recanalization [30][31][32] . Similarly, patients with "slow-growing infarcts" due to good collateral circulation in the (DWI or CTP Assessment with Clinical Mismatch in the Triage of Wake-Up and Late Presenting Strokes Undergoing Neurointervention with Trevo) and DEFUSE3 (Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke 3) trials benefitted from late thrombectomy (6 to 24 h after stroke onset), likely due to sufficient collateral circulation to maintain tissue viability prior to recanalization up to 24 h post stroke [33][34][35][36][37][38][39][40][41][42] .…”
mentioning
confidence: 86%
“…A large area of irreversible infarct and a small area of "ischemic penumbra" or peripheral zone of reversible ischemia is considered a contraindication for endovascular reperfusion due to the risk of hemorrhage and low likelihood of a good outcome. CTP, however, has been shown to be useful in clinical practice because it can elucidate the presence of a large penumbral zone, which is a predictor of good neurologic outcome after reperfusion [10].…”
Section: Discussionmentioning
confidence: 99%